The importance of follow-up and re-diagnosis of patients with demyelinating syndrome suspicion - a case study of a conversion from radiologically isolated syndrome to clinically definite multiple sclerosis - Kulczyński, Marcin; Marciniec, Michał; Sapko, Klaudia; Muñoz-Niklitschek, Esteban (Journal of Education, Health and Sport, 2020)
Introduction. Radiologically isolated syndrome (RIS) is a term to describe criteria of diagnosis for the individuals, who underwent brain MRI because of other reasons than multiple sclerosis (MS) suspicion, but turned out to have white matter lesions similar to those present in patients with diagnosed MS. RIS is a separate entity with the presence of MR detected lesions strongly suggestive of MS in patients with no neurological manifestations. Although RIS is not the first stage of MS in every individual, 30-45% of them will present clinical symptoms later. There is a consensus, that about 1/3 of RIS patients will convert to clinically definite MS (CDMS) within 5 years of follow-up. There are some significant predictors of conversion, such as: age (< 37 when diagnosed), male sex and presence of lesions in spinal cord. Case report. We describe a case of a 35-year-old female patient who was initially diagnosed with RIS after MRI performed due to migraine. After about year and a half of follow-up she presented first clinical manifestation (temporary left eye blindness) followed by second episode (in the second eye), a progression in MRI and appearance of oligoclonal bands in cerebrospinal fluid. Discussion. Among individuals with incidentally found lesions in MRI, only few happen to have white matter findings similar to demyelinating lesions in patients with CDMS. Non-specific MRI white matter lesions are much more often than than those fulfilling 2017 MAGNIMS criteria. There is more research needed to determine significant risk factors for conversion from RIS to CDMS. In RIS patients watchful neurological supervision is indispensable.